Detecting medication errors associated with the use of beta-lactams in the Russian Pharmacovigilance database - Anna V. Kuzmina; Irina L. Asetskaya; Sergey K. Zyryanov; Vitaliy A. Polivanov (BMC, 2021)
Abstract Background Comprehensive analysis of all available data in spontaneous reports (SRs) can reveal previously unidentified medication errors (MEs). Methods To detect MEs, we performed a retrospective analysis of SRs submitted to the Russian pharmacovigilance database in the period from January 01, 2012, to August 01, 2014. This study evaluated SRs of cases where beta-lactam antibiotics were the suspected drug. Results A total of 3608 SRs were analyzed. MEswere detected in 1043 reports (28.9% of all cases). The total number of detected errors was 1214. Reporters themselves indicated MEs in 29 SRs. A term denoting an ME was selected in the "Adverse Reactions" section in 18 of these SRs, whereas in the other 11 reports information on the ME was found only in the "Case narrative" section. MEs were associated with wrong indications in 32.5% of the cases; 61.0% of these cases were viral infections. Various dosing regimen violations constituted 29.7% of MEs. A contraindicated drug was administered in 17.3% of all detected MEs, most commonly to a patient with a history of allergy to the suspected drug or severe hypersensitivity reactions to other drugs of the same group. Conclusion Automatic identification of MEs in the pharmacovigilance database is sometimes precluded by the absence of a code for the respective episode in the "Adverse Reactions" section, even when the error was detected by the reporter. The most frequent types of MEs associated with the use of beta-lactams in Russia are the leading risk factors of growing bacterial resistance.